2017
DOI: 10.18203/2394-6040.ijcmph20171309
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on the knowledge, attitudes and practices towards menstrual cycle and its problems: a comparative study of government and non-government adolescent school girls

Abstract: Background: Young girls up to 20 years of age comprise a quarter of Indian female population. A vast majority of adolescent girls in India are affected by reproductive health issues and menstrual problems are one of them. These problems arise mostly due to false beliefs & poor awareness regarding menstrual cycle. The objective of the study was to assess knowledge, attitude and practices towards menstrual cycle and its problems among school girls. Methods: A cross sectional study among 250 girls (age 13-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 6 publications
9
11
0
Order By: Relevance
“…It is very much similar with the findings of Hakim et al, Kapoor et al, Kansal et al and Udayar et al 9,11,13,14 Pandit et al found majority mothers were completed their middle school flowed by primary school, they observed very less illiterate mothers. 8 Nagar et al found majority mothers were completed high school.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is very much similar with the findings of Hakim et al, Kapoor et al, Kansal et al and Udayar et al 9,11,13,14 Pandit et al found majority mothers were completed their middle school flowed by primary school, they observed very less illiterate mothers. 8 Nagar et al found majority mothers were completed high school.…”
Section: Discussionsupporting
confidence: 89%
“…Nuclear families ere prevalent in current study it is similar with Khanna et al Hakim et al, Pandit et al and Palak et al 7,8,11,12 But Nagar found more family members in their study. 10 Current changing demographic feature in India is more number of nuclear families is emerging even in rural tribal settings.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations